Early versus Delayed Laparoscopic Cholecystectomy for Acute Cholecystitis: A Prospective Randomized Trial. (25th December 2013) - Verma, Sushant; Agarwal, P. N.; Bali, Rajandeep Singh; Singh, Rajdeep; Talwar, Nikhil
Abstract : Introduction . Very few studies demonstrate the feasibility of laparoscopic cholecystectomy for acute cholecystitis. However, most surgeons prefer to delay surgery in the acute phase. The aim of this prospective randomized study was to evaluate the safety and feasibility of laparoscopic cholecystectomy for acute cholecystitis. Materials and Methods . Between August 2010 and March 2012, 30 patients with a diagnosis of acute cholecystitis underwent early laparoscopic cholecystectomy within 72 h of admission. This study group was compared with a control group of 30 patients of acute cholecystitis, who underwent delayed laparoscopic cholecystectomy after an initial period of conservative treatment. Results . There was no significant difference in the conversion rates (3 early versus 2 delayed), postoperative analgesia requirements, postoperative pain scores, or duration of postoperative stay (1.67 days early versus 1.47 days delayed). However, duration of surgery was significantly more in the early group (65.78 minutes early versus 56.83 minutes delayed). Surgery was abandoned in 2 patients from the early group because of difficult anatomy. No complications and mortality were seen in either group. Conclusions . Early laparoscopic cholecystectomy for acute cholecystitis is safe and feasible, offering the additional benefit of a shorter hospital stay. It should be offered to patients with acute cholecystitis, provided the surgery is performed within 72 h from the onset of symptoms.